A new broom sweeps clean: evidence of the inhibiting effects of returnee managers on R&D manipulation. Issue 3 (2nd July 2020) - He, Yanan; Zhang, Xindong; Hao, Panpan; Dai, Xiaoyong
ABSTRACT: This paper aims to examine the inhibiting effects of returnee managers on the R&D manipulation of firms in the Chinese context. Our sample includes stock companies in the Growth Enterprise Market in China from 2009 to 2013. We find that returnee managers can effectively inhibit their company's R&D manipulation. This is driven mainly by their overseas experience obtained in a country with stronger innovation capabilities, which will be more significant when managers possess technological expertise. The results of our study indicate that establishing a manager team that includes these talents may be an effective approach to improving the innovation ability of Chinese enterprises. Further, policymakers should consider providing a favourable policy environment in which returnees can exert their wisdom and potential after they return.